The Jewish people in the first century : historical geography, political history, social, cultural and religious life and institutions. Vol. two - Safrai, Shemuel, 1919-2003.; Stern, M. (Compendia Rerum Iudaicarum ad Novum Testamentum, 1976)
Series: Compendia Rerum Iudaicarum ad Novum Testamentum Section 1 - The Jewish people in the first century Historial geography, political history, social, cultural and religious life and institutions Edited by S. Safrai and M. Stern in cooperation with D. Flusser and W.C. van Unnik Section 2 - The Literature of the Jewish People in the Period of the Second Temple and the Talmud Section 3 - Jewish Traditions in Early Christian Literature